Microecological trade-offs in partial nitritation under different ammonia-based food-to-microorganism ratios - Junwei Yang; Danyang Zhu; Enhui Xu; Linglong Shi; Rui Liu; Donghai Yang; Yu Hua; Xiaohu Dai (Journal of Environmental Chemical Engineering, 2026)

Chlorine dioxide suppresses Aeromonas through thiol oxidation and modulates hepatic redox–immune responses in Aeromonas salmonicida-infected rainbow trout (Oncorhynchus mykiss) - Baorui Cao; Yan Qin; Tianqing Huan; Junran Tan; Enhui Liu; Wei Gu; Gaochao Wang; Kaibo Ge; Yunchao Sun; Datian Li; Peng Fan; Min Liu; et al. (Fish & Shellfish Immunology, 2026)

Effect of explicit intermediate layer on the solution accuracy of the thermal stress for printed circuit heat exchangers with the homogenization method - Xiaoxu Zhang; Zirui Xu; Enhui Li; Yin Tan; Jiyuan Bi; Dan Zheng; Sheng Wang; Ting Ma (Annals of Nuclear Energy, 2026)

Complete genome sequence of watermelon silver mottle virus infecting Momordica charantia L. in China - Zhongshan Chen; Enhui Li; Lele Cai; Duanxiang Xu; Wenli Du; Xiaolin Zeng; Fangluan Gao; Shan Gao (Australasian Plant Pathology, 2026)

Photoreactive bromide ions as overlooked regulators of nanoplastic surface chemistry and aggregation in sunlit seawater - Xinjie Wang; Enhui Jiang; Yining Wang; Jian Zhao; Shuang Xu; Xinghui Xia; Yang Li (Water Research, 2026)

Numerical simulation towards scaling-up industrial Gas-Solid fluidized bed for the separation of clean coal particles - Ying Jia; Mian Zeng; Yong Zhang; Xianqiang Xiong; Huihuang Xia; Enhui Zhou; Ji Xu; Chenlong Duan; Yuqing Feng; Wei Ge (Fuel, 2026)

A novel compound nutrition powder ameliorates scopolamine-induced cognitive impairment via activating the PKA/CREB/BDNF signaling pathway and restoring cholinergic function - Xiaomeng Xu; Zihan Yuan; Enhui Ma; Limin Zhong; Dong Chen; Songyi Lin (Food Bioscience, 2026)

Adipocytes as core drivers of skin aging and novel targets for regeneration - Enhui Wang; Zijun Xu; Yuting Wang; Junbo Wang; Yanfei Jiang; Chunyue Zhao (Biogerontology, 2026)

Self-supported Ni5P4/CoP/Ni-Foam electrode for enhancing hydroxide ion adsorption in supercapacitor applications - Weiwei Wang; Hongliang Wang; Sencheng Cai; Enhui Jin; Xinyu Zhou; Guoyu Jia; Guancheng Xu; Li Zhang (Chemical Engineering Journal, 2025)

Enhancing the identification of malonylation sites using AlphaFold2 and ensemble learning - Linlin Xu; Yuting Qian; Jiayi Yang; Xiaowei Xu; Zhiqiang Li; Yanhan Wang; Enhui Lv; Xingxing Kang; Hongwei Zhang; Yaping Lu; Fei Wang; Xin Liu (Molecular Diversity, 2025)

Whole-genome resequencing reveals selection signatures in China's first rainbow trout (Oncorhynchus mykiss) strain “Shuike No. 1” - Haibing Ma; Gaochao Wang; Tianqing Huang; Enhui Liu; Wei Gu; Gefeng Xu (Aquaculture, 2025)

Acetylcholinesterase-assisted photoelectrochemical solution gated graphene field-effect transistor for organophosphates pesticide detection - Hairui Wang; Enhui Hou; Na Xu; Jianfeng Wu; Shuang Gao; Ping Nie; Xuelin Zhang; Tao Yu; Limin Chang; Jianwei Xie (Food Chemistry, 2025)

Analysis of the mechanism for bubble effect on the movement behavior of separation particle in gas–solid separation fluidized bed based on fluorescence tracing method - Yangfan Xu; Yiming Xu; Chenyang Zhou; Xiaoyang Wei; Feng Lu; Chenlong Duan; Enhui Zhou (Chemical Engineering Journal, 2025)

Multiscale modelling and simulation of coal separation process in a pilot-scale gas–solid fluidized bed - Ying Jia; Yong Zhang; Wei Han; Xianqiang Xiong; Enhui Zhou; Ji Xu; Chenlong Duan; Yuqing Feng; Yuemin Zhao; Wei Ge (Chemical Engineering Journal, 2025)

Particulate fluidization characteristics using Geldart A- particles in gas-solid separation fluidized bed - Ziyuan Li; Yiming Xu; Yangfan Xu; Chenlong Duan; Chenyang Zhou; Enhui Zhou (Chemical Engineering Journal, 2025)

Holographic characterization of typical silicate minerals by terahertz time-domain spectroscopy - Haochong Huang; Xinyu Li; Zhiyuan Zheng; Hanhan Fan; Caiqin Liu; Enhui Yuan; Jialu Gu; Yutong Ma; Qian Xu; Spozmai Panezai; Shanshan Li; Zhuo Zhang; et al. (Applied Clay Science, 2025)

The analysis and optimization of S-CO2 coal fired power generation system using the split method - Yuandong Guo; Enhui Sun; Jinliang Xu; Cheng Chang; Zhaofu Wang (Process Safety and Environmental Protection, 2025)

Evaluation of the acute toxic effects of ammonia on juvenile ussuri cisco (Coregonus ussuriensis) based on histopathology, antioxidant enzyme activity, immune response and the integrated biomarker response - Gefeng Xu; Yucai Pan; Wei Gu; Tianqing Huang; Enhui Liu; Gaochao Wang (Marine Pollution Bulletin, 2024)

Influence of increasing acclimation temperature on growth, digestion, antioxidant capacity, liver transcriptome and intestinal microflora of Ussruri whitefish Coregonus ussuriensis Berg - Kaibo Ge; Ze Fan; Tianqing Huang; Wei Gu; Gaochao Wang; Enhui Liu; Runlei Pan; Datian Li; Yunchao Sun; Zuochun Yao; Liwei Wang; Cheng Zhao; et al. (Fish & Shellfish Immunology, 2024)

Effects of Exogenous Hormones on Spawning Performances, Serum Gonadotropin and Sex Steroid Hormone in Manchurian Trout (Brachymystax lenok) during Sexual Maturation - Yucai Pan; Gefeng Xu; Tianqing Huang; Wei Gu; Enhui Liu; Gaochao Wang (Fishes, 2024)
The objective of this study was to investigate the effects of salmon gonadotropin releasing hormone analog (S-GnRH-A) and human chorionic gonadotropin (HCG) on the serum levels of gonadotropins (GtHs) and sex steroid hormones in Manchurian trout during sexual maturity. Females in the treatment group were injected with 20 µg/kg S-GnRH-A and 400 IU/kg HCG, whilst males were injected with half the amount. Blood samples were collected at 0, 5, 10, and 20 days post injection (dpi). The results showed an increase in female follicle-stimulating hormone (FSH) levels in the treatment group at 5 dpi, and from 5 dpi onwards, a difference was observed between the groups, with higher FSH levels in the treatment group compared to the control group. In males, FSH levels showed group differences at only 5 dpi (p

Development of polymorphic simple sequences repeats markers from whole gene resequencing data comparison of 68 Oncorhynchus mykiss - Haibing Ma; Tianqing Huang; Enhui Liu; Gaochao Wang; Wei Gu; Gefeng Xu (Frontiers in Marine Science, 2024)
Rainbow trout ( Oncorhynchus mykiss ) is a significant cold-water fish farmed in China. Currently, most molecular marker-assisted breeding applications in rainbow trout rely on SSR markers. Although many rainbow trout SSR markers have been developed, methods for mining many polymorphic SSR markers from the genome and identifying them efficiently and rapidly are still lacking. For this reason, this study used in silico simulation method to rapidly develop a large number of polymorphic SSR markers quickly. A total of 354,613 SSR loci with two to six nucleotide repeat motifs were mined from 32 chromosomes of the rainbow trout reference genome using GMATA. The chromosome sequences of the reference genome were then aligned to the whole genome sequencing data (10×) of 68 rainbow trout samples. In silico genotyping was performed using the HipSTR programme to compare and count the variation in the number of repeats of the motifs of the SSR loci in the samples. The loci with high deletion rates and monomorphism were discarded, while those with more than one non-reference allele were kept. The final set of polymorphic SSR loci screened was 78,828. Finally, 4,821 SSR loci were selected with more than 3 alleles and no deletion in all rainbow trout samples and were physically mapped. The average polymorphic information content of these loci was 0.692, indicating high levels of polymorphism. These SSRs were utilized to analyse the genetic diversity and population structure of the 68 rainbow trout samples. The results showed that these 68 samples were divided into two groups. These newly discovered polymorphic SSR markers will provide valuable information for evaluating the construction of rainbow trout family lines for genetic diversity and improvement.

How does top-down water unified allocation and regulation decelerate water utilization? Insights from the Yellow River, China - Lingqi Li; Enhui Jiang; Chang Liu; Chong-Yu Xu (Journal of Cleaner Production, 2024)

Identification and molecular characterization of two liver expressed antimicrobial peptides (LEAPs) in Amur grayling (Thymallus arcticus grubei Dybowski, 1869) - Baorui Cao; Enhui Liu; Tianqing Huang; Wei Gu; Gaochao Wang; Bingqian Wang; Gefeng Xu (Aquaculture, 2024)

Genome-wide identification of simple sequence repeats and development of polymorphic SSR markers in brown trout (Salmo trutta) - Haibing Ma; Tianqing Huang; Wei Gu; Enhui Liu; Gaochao Wang; Bingqian Wang; Jianshe Zhou; Gefeng Xu (Conservation Genetics Resources, 2023)

Single and joint toxic effects of waterborne exposure to copper and cadmium on Coregonus ussuriensis Berg - Wei Gu; Kai Ji; Tianqing Huang; Enhui Liu; Gaochao Wang; Xiulan Shi; Fulin Dong; Bingqian Wang; Xubin Zhang; Xiance Wang; Gefeng Xu (Ecotoxicology, 2023)

Degradation reduces greenhouse gas emissions while weakening ecosystem carbon sequestration of Moso bamboo forests - Ning Yuan; Enhui Wang; Shaofeng Lv; Xiaoping Tang; Tongying Wang; Gang Wang; Yufeng Zhou; Guomo Zhou; Yongjun Shi; Lin Xu (Science of The Total Environment, 2023)

The contribution of earthworms to carbon mineralization during vermicomposting of maize stover and cow dung - Yuxiang Chen; Yan Zhang; Xiong Shi; Enhui Shi; Tingting Zhao; Yi Zhang; Lixin Xu (Bioresource Technology, 2023)